# Precalculus

posted by .

Simplify:[(cscx-cotx)(cscx+cotx)]/cscx

• Precalculus -

[(cscx-cotx)(cscx+cotx)]/cscx

expand

= (csc^2 x - cot^2 x)/csc x

= (1 + cot^2 x - cot^2 x)/csc x
= 1/csc x
= sin x

## Similar Questions

1. ### calculus

express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
2. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
3. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
4. ### Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
5. ### Math

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
6. ### Trigonometry

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
7. ### Math

Perform the multiplication and use the fundamental identities to simplify. (cotx + cscx)(cotx-cscx) I know that you have to foil first so cot^2x - csc^2x and then use the pythagorean identity 1+cot^2u = csc^2u but I do not know how …
8. ### Pre-Cal

Perform the multiplication and use the fundamental identities to simplify. (cotx + cscx)(cotx-cscx) I know that you have to foil first so cot^2x - csc^2x and then use the pythagorean identity 1+cot^2u = csc^2u but I do not know how …
9. ### ap calc bc

hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct?
10. ### trig

Prove (cscx+cotx)(cscx-cotx)=1

More Similar Questions